What Do You Believe In? French Translation of the FAD-Plus to Assess Beliefs in Free Will and Determinism and Their Relationship with Religious Practices and Personality Traits. Issue 1 (20th February 2017) - Caspar, E. A.; Verdin, O.; Rigoni, D.; Cleeremans, A.; Klein, O.
The influence of (dis)belief in free will on prosocial behaviors and sense of control has attracted considerable interest over the last few years. The provision of relevant research tools to assess beliefs in free will and determinism for the community thus becomes a central endeavour. However, no relevant validated questionnaires are currently available to the French language community. Therefore, the present study was aimed at providing a valid French translation of the FAD-plus (Paulhus & Carey, 2011 ), a questionnaire built to assess people's beliefs in Free will and Determinism. Exploratory factor analysis of the data obtained in Sample 1 revealed a four factor model. Confirmatory factor analyses on the basis of Sample 2 data were conducted to compare the theoretical model advanced by Paulhus and Carey's versus the model obtained in Sample 1. With only but a few modifications as compared to the original questionnaire, the questionnaire that we here propose appears to constitute a reliable tool for the French language community. We also examined the relationship between beliefs in free will, determinism and religious practices. We found that the more people are engaged in religious practices, the more they believe in determinism and in the inevitability of their future.